The Association Between Internal Governance Mechanisms And Corporate Value: Evidence From Bahrain - Gehan A. Mousa; Abdelmohsen M. Desoky (Asian Academy of Management Journal of Accounting and Finance, 2012)
This research investigates the effect of internal corporate governance mechanisms (e.g. board characteristics and ownership structure) on corporate value. The paper extends the previous literature in this area and provides evidence to this effect using a sample of listed companies on the Bahrain Stock Exchange (BSE). In addition to Pearson correlation, this paper employs the Ordinary Least Square (OLS) regression analysis to test the association between board characteristics and ownership structure as independent variables and corporate value (the dependent variable) measured by three different measures namely Tobin's Q; return on assets (ROA); and earnings per share (EPS). Statistical analysis, three models of OLS regression, revealed that board characteristics and ownership structure variables have a statistically significant effect on corporate value especially when measured by EPS. The scope of this study is limited to relatively listed companies on BSE. Finally, it would be interesting to duplicate this study in other countries, which have many similarities to the Bahraini environment.